Simultaneous topography-guided photorefractive keratectomy with accelerated collagen cross-linking in the treatment of stage I keratoconus - A. V. Ivanova; A. S. Sklyarova; K. B. Letnikova; A. T. Khandzhyan; N. V. Khodzhabekyan (Российский офтальмологический журнал)
Purpose: to evaluate the efficiency of simultaneous topography-guided photorefractive keratectomy (PRK) with accelerated collagen cross-linking in the treatment of stage I keratoconus.Material and methods. 38 patients (49 eyes) aged 18 to 44 with stage I keratoconus were treated with simultaneous topography-guided PRK combined with accelerated corneal collagen crosslinking. Along with standard ophthalmological testing, patients underwent aberrometry, confocal microscopy, optical coherence tomography of the cornea, imaging of the anterior eye section on a Scheimpflug analyzer, and examination of the biomechanical properties of the cornea. The follow-up period was 2 years.Results. Two years after surgery, uncorrected visual acuity which originally was 0.23 ± 0.03 showed a statistically significant increase and reached 0.72 ± 0.02; best corrected visual acuity improved from 0.44 ± 0.03 to 0.89 ± 0.02; the refractive power of the cornea fell from 45.03 ± 0.28 to 42.55 ± 0.31 D; the spherical component of refraction reduced from -2.00 ± 0.19 to -0.73 ± 0.09 D; the cylinder component reduced from 2.46 ± 0.14 to 0.79 ± 0.07 mm, the thinnest point of the cornea reduced from 486.30 ± 4.78 to 406.80 ± 6.51 μm. The highest order aberrations showed the following results: Coma index reduced from 0.27 ± 0.12 to 0.08 ± 0.07, Tilt reduced from 0.53 ± 0.11 to 0.10 ± 0,09, and Trefoil reduced from 0.13 ± 0.04 to 0.05 ± 0.02.Conclusion. The analysis of clinical and functional results, biomechanical properties and structures of the cornea confirmed the efficacy and safety of the combined treatment of patients with stage I keratoconus.